Morphology and thermal stability of silk fibroin/starch blended microparticles (eXPRESS Polymer Letters, 2010)
In the present study biodegradable microparticles of silk fibroin (SF)/starch blends were prepared by a simple water-in-oil emulsion solvent diffusion technique. SF/starch blended solution and ethyl acetate were used as water and oil phases, respectively. The influence of SF/starch ratios on characteristics of the blended microparticles was investigated. The SF conformation of microparticle matrices from FTIR analysis was changed from random coil to β-sheet form by blending with starch. The blended microparticles had lower dissolution in water than those of SF and starch microparticles. The 1/3 (w/w) SF/starch blended microparticles exhibited the lowest dissolution. The SF and starch microparticles showed irregular and deflated shapes, respectively. The blended microparticles were nearly spherical in shapes and smaller sizes. Thermal stability of the blended microparticles slightly increased with the starch blended ratio. The results suggested that SF conformational transition, thermal stability, morphology and dissolution of the blended microparticles can be adjusted by varying the blended ratio.